Papers and Posters Presented at the International Congress on Health and Wine. Wine as Part of a Healthy Diet and Lifestyle - Congress, International (South African Journal of Enology and Viticulture, 2017)
Papers and Posters Presented at the International Congress on Health and Wine.  Wine as Part of a Healthy Diet and Lifestyle, 13 - 16 September 2005, Spier, Stellenbosch, South Africa.